Study of a poly(vinylidene fluoride)/hydrophobic silica sol hybrid hollow fiber membrane for treatment of produced water via direct contact membrane distillation. (December 2021) - Zou, Lusi; Zhang, Yu; Yu, Jianjia; Zha, Shangwen; Guan, Rong; Jiang, Shufang
Abstract: Direct contact membrane distillation (DCMD) has shown great promises in remediating high-salinity oilfield produced water (PW). In our previous work, a hydrophobic silica sol (Si-R) was successfully synthesized to engineer anti-wetting ability of poly(vinylidene fluoride) (PVDF) membrane. Here our research interest lies in customizing PVDF hollow fiber membrane (HFM) with desirable stability for treating challenging oilfield PW via a DCMD process. The PVDF/Si-R hybrid HFM was fabricated under an optimized spinning condition. It is found that the fabricated PVDF/Si-R HFM is sandwich-structured, consisting a highly porous and thick middle layer and small-size macrovoids of outer layer and inner layer with different pore geometry, and the unique sandwich structure endows the membrane with superior wetting resistance. The membrane characterization showed that the liquid entry pressure (LEP) and water contact angle (WCA) of the fabricated PVDF/Si-R HFM impressively reached up to 5.25 bar and 126°, respectively. As a result, the PVDF/Si-R HFM possessed a desirable performance in treating high-salinity oilfield PW in terms of wetting resistance and salt rejection. Specifically, with a 60 h continuous DCMD operation, the PVDF/Si-R membrane exhibited over 99.9% salt rejection with only 7% reduction in permeate water flux. Clearly, the synthesized hydrophobic Si-R is a favorable additive for enhancing the antiwetting ability of PVDF HFM to treat high-salinity oilfield PW via DCMD process.